PENGARUH STATUS PENGUASAAN LAHAN TERHADAP PENDAPATAN PETANI PADI DI DESA TUMANI, KECAMATAN MAESAAN, KABUPATEN MINAHASA SELATAN - Meike Prisilia Manatar; Esry H. Laoh; Juliana R. Mandei (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine whether there is influence over land tenure status to the income of rice farmers. Data retrieval is done with primary data and secondary data. Primary data were obtained from the farmers through a list of questions that had been prepared, while secondary data obtained from the office of the village or the head of the village. The way of taking samples, to look at the total population of each of the existing land tenure status, then divided by the population over land ownership and divided by 60 as a sample to be taken. The data collection method used is descriptive analysis and ANOVA (analysis of variance) in one direction. The concepts of measuring variables used are over land ownership, production, farming costs, revenue and income. The results of this study indicate that there are significant land ownership to farmers' income, the highest income is income tenants. Different income is the income of farmers own property with tenant farmers' income.